2023
DOI: 10.3389/fgene.2022.1082985
|View full text |Cite
|
Sign up to set email alerts
|

Addressing disparities in pharmacogenomics through rural and underserved workforce education

Abstract: Introduction: While pharmacogenomic (PGx) testing is routine in urban healthcare institutions or academic health centers with access to existing expertise, uptake in medically-underserved areas is lagging. The primary objective of this workforce education program is to extend access to didactic, case-based and clinical PGx training for pharmacists serving rural Minnesota and populations experiencing health disparities in Minnesota.Methods: A PGx workforce training program funded through the Minnesota Departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…47 It is worth noting that a lack of access to PGx testing is also a known issue in high income countries, as several studies in the United States have reported that rural populations have limited access to PGx testing and PGx-trained HCPs compared to people residing in metropolitan areas, due to the fact that most PGx services have been limited to larger institutions. 48,49 In the study conducted by Nagy et al in Egypt, they reported cultural or religious beliefs as a barrier to adoption of PGx in oncology practice, which was not identified in the other studies included in this review; however, this barrier was not further explained by the authors. These findings highlight that a unique set of challenges exist in different regions, and further studies outside of the United States, particularly in emergent nations and within different health system constructs, are required to better understand patients and practitioners' viewpoints and education needs in oncology PGx relevant to the local context.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…47 It is worth noting that a lack of access to PGx testing is also a known issue in high income countries, as several studies in the United States have reported that rural populations have limited access to PGx testing and PGx-trained HCPs compared to people residing in metropolitan areas, due to the fact that most PGx services have been limited to larger institutions. 48,49 In the study conducted by Nagy et al in Egypt, they reported cultural or religious beliefs as a barrier to adoption of PGx in oncology practice, which was not identified in the other studies included in this review; however, this barrier was not further explained by the authors. These findings highlight that a unique set of challenges exist in different regions, and further studies outside of the United States, particularly in emergent nations and within different health system constructs, are required to better understand patients and practitioners' viewpoints and education needs in oncology PGx relevant to the local context.…”
Section: Discussionmentioning
confidence: 83%
“…47 It is worth noting that a lack of access to PGx testing is also a known issue in high income countries, as several studies in the United States have reported that rural populations have limited access to PGx testing and PGx‐trained HCPs compared to people residing in metropolitan areas, due to the fact that most PGx services have been limited to larger institutions. 48 , 49 In the study conducted by Nagy et al. in Egypt, they reported cultural or religious beliefs as a barrier to adoption of PGx in oncology practice, which was not identified in the other studies included in this review; however, this barrier was not further explained by the authors.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The universal shortage of genomic specialists requires that healthcare providers and policymakers seek for novel and sustainable solutions regarding widespread implementation of germline testing. This is in addition to the need for streamlining educational efforts regarding implications of genetic testing, especially for prevention and targeted therapeutics ( Al-Sukhun et al, 2023 ; Brown et al, 2023 ; Moyo et al, 2023 ). Implementation of a systematic guide like the ACCESS framework, and partnering with the nursing workforce who is a major stakeholder in promoting health equity, may facilitate initiatives such as the Rare Genomes Project (RGP) ( Serrano et al, 2023 ) and the Genomic Answers for Kids (GA4K) ( Kane et al, 2023 ) reduce barriers and inequalities for underrepresented patients with rare genomic disorders and for children, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, continued efforts are needed to develop effective learning curricula and practice experiences to insure pharmacists possess the skills and knowledge to integrate PGx into practice [149][150][151]. For pharmacists in advanced training [152] as well as practicing pharmacists, a number of novel approaches have been developed, including experiential learning, online learning, clinical decision support and patient educational materials, and networks of PGx experts [78,[153][154][155][156][157]. In particular, several schools and professional organizations have developed participatory or experiential learning opportunities for PGx testing [158][159][160][161].…”
Section: Enhancing Pgx Content In the Pharmacy Curricula And Continue...mentioning
confidence: 99%